The Curious Case of the De-ICD: Negotiating the Dynamics of Autonomy and Paternalism in Complex Clinical Relationships. Issue 8 (2nd August 2016) - Pullman, Daryl; Hodgkinson, Kathleen
Abstract : This article discusses the response of our ethics consultation service to an exceptional request by a patient to have his implantable cardioverter defibrillator (ICD) removed. Despite assurances that the device had saved his life on at least two occasions, and cautions that without it he would almost certainly suffer a potentially lethal cardiac event within 2 years, the patient would not be swayed. Although the patient was judged to be competent, our protracted consultation process lasted more than 8 months as we consulted, argued with, and otherwise cajoled him to change his mind, all to no avail. Justifying our at times aggressive paternalistic intervention helped us to reflect on the nature of autonomy and the dynamics of the legal, moral, and personal relationships in the clinical decision-making process.